Kānprachum wichākān radap chāt Mō̜.ʻŌ̜Bō̜. wičhai khrang thī 2, 28-29 Karakadākhom 2551, Mahāwitthayālai ʻUbon Rātchathānī ([Mahāwitthayālai ʻUbon Rātchathānī], 2008)
Collection of research abstracts of the 2nd academic conference papers on humanities and social sciences, held in July 2008 by Ubon Ratchathani University, Ubon Ratchathani Province, Northeastern Thailand.